2022
DOI: 10.1182/bloodadvances.2022007009
|View full text |Cite
|
Sign up to set email alerts
|

Code status transitions in patients with high-risk acute myeloid leukemia

Abstract: Patients with high-risk acute myeloid leukemia (AML) often experience intensive medical care at the end of life (EOL) including high rates of hospitalizations and intensive care unit admissions. Despite this, studies examining code status transitions are lacking. We conducted a mixed-methods study of 200 patients with high-risk AML enrolled in supportive care studies at Massachusetts General Hospital between 2014-2021. We defined high-risk AML as relapsed/refractory or diagnosis at age ≥60. We used consensus-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Another study of 200 leukemia patients reported the median time from last code status transition to death was only two days. Thirty-two percent (32%) of those code status conversations occurred at the time of clinical deterioration and 39.5% Current Treatment Options in Oncology without the patient present or capable of making their own medical decisions [73]. Thus, there are significant opportunities for improvement in advance care planning and symptom management in acute leukemia care.…”
Section: Symptom Burden and Palliative Care Needsmentioning
confidence: 99%
“…Another study of 200 leukemia patients reported the median time from last code status transition to death was only two days. Thirty-two percent (32%) of those code status conversations occurred at the time of clinical deterioration and 39.5% Current Treatment Options in Oncology without the patient present or capable of making their own medical decisions [73]. Thus, there are significant opportunities for improvement in advance care planning and symptom management in acute leukemia care.…”
Section: Symptom Burden and Palliative Care Needsmentioning
confidence: 99%
“…Blood cancers can be aggressive and rapidly fatal; or, blood cancers may have a relapsing and remitting course for which multiple, effective lines of therapy are available, making it hard to determine prognosis 9 10. As a result, clinicians may be less willing to institute EOL care and timely level of intervention (LOI) discussions or consultation with palliative care (PC) 11–15…”
mentioning
confidence: 99%